Analysis of Achievement of Malaria Elimination Maintenance in Sorong Selatan District - Maya Rante Allo; Ishaq Iskandar; Arlin Adam; Zamli (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: . The goal of malaria control in Indonesia is to achieve gradual elimination by 2030, starting from the district/city, provincial, regional, and national levels. The process will begin with elimination assessments for Java and Bali in 2023; Sumatra, Nusa Tenggara Barat (NTB), and Sulawesi in 2025; Kalimantan and Maluku Utara in 2027; Nusa Tenggara Timur (NTT) and Maluku in 2028; Papua Barat and Papua in 2029; with national elimination certification expected by 2030 Objective: . This study aims to understand the inputs, activities, and outputs conducted by South Sorong District in maintaining malaria elimination Method: The method used is a qualitative approach with interviews conducted with nine informants, including healthcare workers and community members. Result: The results of this study indicate that in South Sorong District, trained healthcare workers and cross-professional collaboration play a crucial role in malaria elimination, despite limited numbers and funding from APBN, APBD, and the Global Fund. The Bela Kampung program raises community awareness, supported by routine monitoring and control activities such as blood surveys and the distribution of insecticide-treated nets. The district has successfully maintained its malaria elimination status despite challenges such as community dishonesty and budget constraints. Optimizing community awareness, cross-sector collaboration, the commitment of the regent, and program innovation help address these challenges. Conclusion: The study recommends increasing the number of healthcare workers and strengthening cross-sector collaboration to maintain malaria elimination in South Sorong District. Additionally, increasing funding and ongoing support from the local government are necessary.